Alternative HPLC-DAD Direct-Phase Approach to Measurement of Enantiopurity of Lactic Acid Derivatives - Maria Montrone; Cosimo Cardellicchio; Maria Annunziata M. Capozzi (Applied Sciences)
Lactic acid (LA) is a natural organic acid that can be used in a wide variety of industries. Recently, the production of lactic acid by fermentation protocols has gained relevance. However, these biotechnological processes often encounter challenges in the production of enantiopure D- or L-lactic acid. Thus, the measurement and control of the enantiopurity of lactic acid and its derivatives is a crucial step in these productions, especially when monomers have to be used to synthesize polymers, such as polylactic acid (PLA). In the present work, we propose a measurement of the enantiopurity of lactic acid mixtures with HPLC-DAD by using direct-phase conditions, which are mild, and a large set of different employable chiral columns. To this end, we report the synthesis of two new LA derivatives (2-nitrobenzyl 2-hydroxypropanoate and 2,4-dinitrobenzyl 2-hydroxypropanoate) and benzyl 2-hydroxypropanoate, with a selective and non-racemizing chemical functionalization. Then, three commercially available HPLC direct-phase chiral columns are tested to achieve a method for measuring the enantiomeric purity of lactic acid derivatives. The 2-nitrobenzyl lactate was chosen as the best lactic acid derivative and the Chiralpak IA column was chosen as the most effective chiral column to achieve a new and efficient protocol (Rs = 3.57 and α = 1.13) for the measurement of the enantiopurity of lactic acid.